Post‐Malthusian Dynamics in Pre‐Industrial Scandinavia1. (9th August 2016) - Klemp, Marc; Møller, Niels Framroze
Abstract: Theories of economic growth hypothesize that the transition from pre‐industrial stagnation to sustained growth is associated with a post‐Malthusian phase in which technological progress raises income and spurs population growth while offsetting diminishing returns to labor. Evidence suggests that England was characterized by post‐Malthusian dynamics preceding the Industrial Revolution. However, given England's special position as the forerunner of the Industrial Revolution, it is unclear if a transitory post‐Malthusian period is a general phenomenon. Using data from Denmark, Norway, and Sweden, this research provides evidence for the existence of a post‐Malthusian phase in the transition from stagnation to growth in Scandinavia.